Anticoagulation in preterm and term neonates: Why are they special?. Issue 187 (March 2020) - Bhat, Rukhmi; Monagle, Paul
Abstract: The preterm and term neonatal population is most at risk for thrombotic complications in pediatrics. Among various treatment modalities, anticoagulation is primarily used in the management of thrombosis. Developmental differences in preterm and term infants compared to older infants and children and limitations of anticoagulation agents currently used are important considerations for treatment. Additionally, dosages and durations of anticoagulant treatment are widely variable across countries. This article will highlight the differences in anticoagulation in neonates compared to other populations due to developmental hemostatic changes, epidemiology of neonatal thrombosis, pharmacokinetic and pharmacodynamic properties of drugs used and presence of neonatal co-morbidities. Highlights: Developmental differences in neonates affects pharmacokinetic and pharmacodynamic properties of anticoagulants. Anticoagulation in neonates needs to be individualized based on the underlying clinical context. Pediatric clinical trials for newer anticoagulant agents have excluded the preterm population where thrombosis is more frequent.